Osteoporosis and Related Health Status Among the Elderly Urban Residents in Elderly-Care Inns in Beijing, a Multicenter DXA Survey - Lin, XinChao; Guo, HongTao; Lian, YiGang; Kou, Jiajing; Wang, GuangLei; Chen, YiYun; Wang, Juan; Han, Xu; Jiang, Miao; Yang, QiaoHui (Frontiers in Endocrinology, 2022)
Background Identification of the high risk population for osteoporosis and timely prevention are the best strategies at present. Detailed epidemiological investigation in a well-defined population is necessary to explore the population-based characteristics and risk factors of osteoporosis, thus to facilitate better prevention programs. Method In this prospective cross-sectional study, 1,423 questionnaires were given out to the urban residents (female ≥ 40 years of age, male ≥50 years) who lived in the 27 Elderly-Care Inns interspersed among the 7 central urban areas of Beijing. All participants were voluntary and underwent routine physical examination and spine and hip BMD measurements using the DXA instrument. The study protocols were approved by the Medical Ethics Committee of Beijing Dongzhimen Hospital (JDZX2015079). Results Altogether 1407 participants fulfilled the survey. Among 359 men, the prevalence of osteoporosis, osteopenia, and normal BMD were 18.1%, 56.6%, and 25.3%, respectively; among 1048 women, the corresponding figures were 40.3%, 42.8%, and 16.9%, respectively. After adjustment of age and BMI, both hands grip strength, height loss over 3 cm, serum levels of β-CTx, PINP, and OST were the independent risk factors for osteoporosis in both men and women; besides, familial Alzheimer disease history in men; and history of steatohepatitis and fracture, serum levels of PTH and ALT, age of menarche, age of menopause, duration of menstruation in women, were also risk factors of osteoporosis. In both genders, the cost-effective method, which adopted both hands grip strength, height loss over 3 cm, and medical history, indicated a good predictive ability to evaluate the risk of osteoporosis (in men AUC=0.730, 95%CI=0.642 0.817; in women AUC=0.769, 95%CI=0.724 0.813). Conclusions In the population of elderly Beijing urban residents in Elderly-Care Inns, the prevalence of osteoporosis in women is higher than that in men, and increases with aging more rapidly; the prevalence of osteopenia in men keeps higher than women. The cost-effective method, including both hands grip strength, height loss over 3 cm, and familial Alzheimer disease history in men; fracture and steatohepatitis history and menstrual history in women, is recommended in identifying the high-risk subjects for osteoporosis.